1988
DOI: 10.1172/jci113411
|View full text |Cite
|
Sign up to set email alerts
|

Role of adhesive proteins in platelet tumor interaction in vitro and metastasis formation in vivo.

Abstract: Platelet-adhesive protein-tumor cell interaction was studied in vitro and in vivo. Monoclonal antibody 1OE5, which inhibits binding of fibronectin and von Willebrand factor to the platelet membrane glycoprotein GPIIb-GPIIIa complex, inhibited the binding of mouse CT26 and human HCI8 colon carcinoma cells to platelets by 63-65%, whereas an irrelevant monoclonal antibody, 3B2, had no effect. Monoclonal antibody 6D1, which inhibits binding of von Willebrand factor to GPIb, also had no effect. RGDS, a tetrapeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
230
2
9

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(254 citation statements)
references
References 25 publications
11
230
2
9
Order By: Relevance
“…[16][17][18] Pretreatment of either tumor cells or platelets with an antibody or peptide that neutralizes vWF or blocks vWF-capable receptors (eg integrins GPIIb/ IIIa and GPIb-present on numerous tumor cell lines) has been shown to inhibit tumor cell-platelet interaction in vitro for colon carcinoma, Walker 256 carcinosarcoma, melanoma and osteosarcoma cell lines (including SAOS2). 19,[44][45][46][47][48][49][50][51][52] Notably, treatment with monoclonal anti-vWF antibody significantly decreased tumor cell metastases in vivo for colon, Lewis bladder and melanoma carcinoma cell 53 suggested that this tumor cell-platelet mechanism may be partially responsible for the common metastasis of osteosarcoma to the lung. In support of this, the osteosarcoma cell lines MG63, HOS, U2-OS, TE-85 and SAOS2 have been shown to induce platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Pretreatment of either tumor cells or platelets with an antibody or peptide that neutralizes vWF or blocks vWF-capable receptors (eg integrins GPIIb/ IIIa and GPIb-present on numerous tumor cell lines) has been shown to inhibit tumor cell-platelet interaction in vitro for colon carcinoma, Walker 256 carcinosarcoma, melanoma and osteosarcoma cell lines (including SAOS2). 19,[44][45][46][47][48][49][50][51][52] Notably, treatment with monoclonal anti-vWF antibody significantly decreased tumor cell metastases in vivo for colon, Lewis bladder and melanoma carcinoma cell 53 suggested that this tumor cell-platelet mechanism may be partially responsible for the common metastasis of osteosarcoma to the lung. In support of this, the osteosarcoma cell lines MG63, HOS, U2-OS, TE-85 and SAOS2 have been shown to induce platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The aggregation of tumor cells and platelets may assist in metastasis by producing a mixed platelet-tumor cell mass that supports adherence of tumor cells to the blood vessel wall and protects the tumor cells from destruction by the immune system. [16][17][18][19][20] In this study, we investigated the disposition of vWF in osteosarcoma through the analysis of messenger RNA (mRNA) and protein expression in tumor samples. Our results suggest that inappropriate expression of the vWF gene occurs during the metastatic spread of osteosarcoma.…”
mentioning
confidence: 99%
“…Platelets adhesion molecules are involved in mediation of platelet-tumor cell interactions. Since GPIIb/IIIa complex was convincingly shown to mediate this process, platelets antagonist based on its inhibition are being tested [5]. The antagonists of GPIIb/IIIa can be divided into RGD-mimicking nanopeptides and monoclonal antibodies binding this complex.…”
Section: Platelets As Therapeutic Targets For Anti-cancer Therapiesmentioning
confidence: 99%
“…5,6]. Experimentally induced thrombocytopenia (depletion of platelets) was shown to reduce the development of metastasis both in transplant and syngeneic mouse tumor models [7].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence provides strong support for the concept that platelets facilitate the hematogenous dissemination of tumor cells, the most convincing of which is the inhibition of metastasis by experimental platelet depletion and the reconstitution of metastatic potential after platelet repletion (16,19). It is believed that platelets provide a protective shield against cytotoxic immune cells (32) and facilitate tumor cell extravasation by potentiating tumor cell adhesive interactions with ECM proteins of the vessel wall (9,13).…”
mentioning
confidence: 99%